The production of bagasse biofuel briquettes and the evaluation of natural binders (LNFC, NFC, and lignin) effects on their technical parameters. (1st January 2021) - Afra, Elyas; Abyaz, Ali; Saraeyan, Ahmadreza
Abstract: This study was carried out in order to assess the fuel briquettes produced from two particle sizes from ground and shredded bagasse. Nano-lignocellulosic binders including nano-lignocellulose, nano-cellulose and lignin, were used at 3, 6 and 9 %w/w to improve the mechanical and thermal properties. Briquettes were produced by densification process with a cylinder-piston system at 150 MPa and 100 °C. It was found that the nano-lignocellulose and nano-cellulose binders were more effective on the physical and mechanical properties than the lignin binder. Lignin binder, however, showed better thermal properties in the briquettes due to its high calorific value. It was found that at 9% of nano-lignocellulose, the compressive strength, the calorific value, fixed carbon, volatile matters and ash for shredded bagasse briquettes were 34 N mm, 29 Mj/Kg, 14.49%, 72.19% and 4% as well as for ground bagasse briquettes were 29.45 N mm, 19.85 Mj/Kg, 13.81%, 72.57% and 7% respectively.